Letramentos acadêmicos para implementar o inglês como meio de instrução na Universidade Federal de Santa Maria - Pretto, Amanda de Mendonça (2020)
Considering the internationalization of higher education, the implementation of actions such as the program Languages without Borders (LwB) and the development of the Institutional Project for Internationalization at the Federal University of Santa Maria, (Universidade Federal de Santa Maria, UFSM), the objective of this work is to map the academic literacies relevant to the adoption of EnglishMedium Instruction (EMI) at the institution, based on perceptions of the professors. In order to carry out this investigation, a questionnaire with open and closed questions was sent to all professors of higher education at UFSM, through the Questionnaire Portal. The instrument looks for quantitative and qualitative data, considering the profile of the professors, their experiences with the English language, their positioning in relation to the adoption of EMI, the difficulties to adopt EMI and the academic literacy practices necessary for this internationalization action. The results indicated that, even in different measures, professors in all teaching centers and campuses at UFSM are interested in EMI. Professors are concerned about adopting EMI, considering how English can make it difficult for students to have access to the university. In addition, the data points to the concern of professors in developing classes that are more interactive. The results also point to the professors’ interest in developing oral academic literacies in all centers and campuses at UFSM.